Engineering Strategies to Boost Crop Productivity by Cutting Respiratory Carbon Loss. Issue 2 (15th October 2019) - Amthor, Jeffrey S.; Bar-Even, Arren; Hanson, Andrew D.; Millar, A. Harvey; Stitt, Mark; Sweetlove, Lee J.; Tyerman, Stephen D.
Abstract: Roughly half the carbon that crop plants fix by photosynthesis is subsequently lost by respiration. Nonessential respiratory activity leading to unnecessary CO2 release is unlikely to have been minimized by natural selection or crop breeding, and cutting this large loss could complement and reinforce the currently dominant yield-enhancement strategy of increasing carbon fixation. Until now, however, respiratory carbon losses have generally been overlooked by metabolic engineers and synthetic biologists because specific target genes have been elusive. We argue that recent advances are at last pinpointing individual enzyme and transporter genes that can be engineered to (1) slow unnecessary protein turnover, (2) replace, relocate, or reschedule metabolic activities, (3) suppress futile cycles, and (4) make ion transport more efficient, all of which can reduce respiratory costs. We identify a set of engineering strategies to reduce respiratory carbon loss that are now feasible and model how implementing these strategies singly or in tandem could lead to substantial gains in crop productivity.